Increasing aridity affects soil archaeal communities by mediating soil niches in semi-arid regions - MukeHuang; Liwei Chai; Dalin Jiang; Mengjun Zhang; Yanran Zhao; Yi Huang (Science of The Total Environment, 2019)
Soil archaea plays a vital role in the functioning of dryland ecosystems, which are expected to expand and get drier in the future as a result of climate change. However, compared with bacteria and fungi, the impacts of increasing aridity on archaea in these ecosystems remain largely unknown. Here, soil samples were collected along a typical aridity gradient in semi-arid regions in Inner Mongolia, China, to investigate whether and how the increasing aridity affects archaeal communities. The results showed that archaeal richness linearly decreased with increasing aridity. After partialling out the effects of soil properties based on partial least squares regression, the significant aridity-richness relationship vanished. The composition of archaeal communities was distributed according to the aridity gradient. These variations were largely driven by the changes in the relative abundance of Thaumarchaeota, Euryarchaeota and unclassified phyla. Niche-based processes were predominant in structuring the observed archaeal aridity-related pattern. The structural equation models further showed that aridity indirectly reduced archaeal richness through improving soil electrical conductivity (EC) and structured community composition by changing soil total nitrogen (TN). These results suggested that soil salinization and N-losses might be important mechanisms underlying the increasing aridity-induced alterations in archaeal communities, and highlighted the importance of soil niches in mediating the indirect impacts of increasing aridity on archaea.
Keywords: Archaea; Aridity; Semi-arid regions; Soil niches